An Outline of the History of Consumer Credit - Press.Gleb Novikov (Journal of Economic Sociology, 2017)
This overview presents the characteristics and an analysis of historical forms of consumer crediting. The theoretical basis of the overview is rooted in the cultural and social history of consumer credit—a new and interdisciplinary direction. Because a distinct emphasis is placed on the differences between forms of crediting in certain countries and historical periods, the cultural and social history of credit appears to be the most appropriate for considering forms of consumer credit as they change throughout history.It also focuses on the history of credit institutional conditions that shaped current forms of crediting. The conditions include legislation regulating debt relations more or less rigorously and forms of credit that have already existed, such as pawnshops, small loans, installment credits, family loans, and open-book credits. Furthermore, the development of consumer credit in the USA and in Europe is analyzed. In the USA, the key processes have been the legalization and legitimation of small loans, the proliferation of installment purchases, and the evolution of credit accounting, whereas in Europe, check credit systems (particularly that which was realized in the United Kingdom by the Provident Clothing and Supply Company) that have no analogues in America are of major interest. Then, the criticisms of credit are taken into account as they appeared throughout its development. The main directions of the counteractions were ethical, anti-capitalist, and anti-American criticism. In the conclusion, it is indicated that research in the history of credit is relevant to both the economists and sociologists in the field and to improving our understanding of the complexity and ambiguity of the various factors that have shaped what we now know as consumer crediting.